간호대학생의 치매지식, 치매태도, 노인돌봄태도가 노인부양의식에 미치는 영향 - 이은미(Lee, Eun Mii); 김민경(Kim, Min Kyung); 정승수(Jung, Seung Su); 손용석(Son, Yong Seok); 고민영(Go, Min Young); 김수진 (Nursing and Health Issues(간호와 보건연구), 27(1), 2022)
Purpose: The purpose of this study was to investigate the effects of knowledge and attitude on dementia, and elderly caring attitude on the awareness of supporting the elderly in nursing students. Methods: Participants were 135 nursing students in A city. Data was collected from May 17 to 31, 2021. Data analysis was conducted using one-way ANOVA independent t-test, Pearson’s correlation coefficient, and multiple regressions analysis in SPSS, version 21.0. Results: Students’ attitudes toward dementia(=.46, p<.001), and a background of living together with grandparents (=−.32, p<.001) were responsible for creating in them an awareness of elderly support and care. The total explanatory power was 40.7%. Conclusion: There is a need for a support system to help strengthen people’s positive attitudes toward dementia and serve as a strategy to bring changes in the awareness of elderly support among nursing students. KCI Citation Count: 1